الكتابة الجاوية أداة لإسلامية المعرفة: Jawi Writing as a Tool for Islamization of Knowledge - Hakim, Amani; Ahmad H. Osman, Rahmah; Mohamad, Amira Hanin; Zainal, Hakim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص الكتابة الجاوية هي إحدى الميزات التي امتلكها المسلمون في أرخبيل الملايو خاصة والماليزيون عامة وذلك لأن الكتابة الجاوية عبارة عن انعكاس تام للغة العربية حيث إنهما متشابهتين في الكتابة والحروف رغم اختلافهما من حيث القراءة ، إن اللغة العربية لغة ترمز للهوية الإسلامية. بيد أن موقف الكتابة الجاوية يواجه تحديًا متزايدًا مع إدخال نظام الكتابة الجديدة القائم على الحروف اللاتينية وقد جعل الاستعمار المجتمع في ماليزيا يستخدمها ويفضلها عن الكتابة الجاوية. وهذا يؤدي إلى نقص الاهتمام لدى الأجيال القادمة بشأن إتقان الكتابة الجاوية ومعرفة قراءة الحروف والكتابات المستوحاة من الحروف العربية. لذا تهدف هذه الدراسة إلى دراسة تاريخ الكتابة الجاوية وإبراز مدى أهمية اعتبار هذه الكتابة أداة لإسلامية المعرفة في ماليزيا. وتوصل البحث إلى وجود العلاقة القوية بين الكتابة الجاوية في عملية إسلامية المعرفة واللغة من خلال اسهاماتها في نشر العلوم الدينية للمجتمع المسلم الماليزي ووجود الجهود المبذولة من قبل الفئات المتعددة في الحفاظ على الكتابة الجاوية. Abstract The Javanese writing is one of the privileges possessed by Malaysians in general and Muslims in particular, because the Javanese writing is a complete reflection of the Arabic language, as it is similar in writing and letters despite the difference in terms of reading the Arabic language, a language that symbolizes Islamic identity. However, the situation of Javanese writing is increasingly challenged with the introduction of a new writing system based on the Latin script and making people use and prefer it from Javanese script. This leads to a point of concern regarding the mastery of Javanese writing in future generations and their knowledge of reading letters and writings inspired by Arabic letters. Therefore, this study aims to study the history of Javanese writing and to highlight the extent to which this writing serves as a tool for Islamic knowledge in Malaysia. The research concluded that there is a strong relationship between Javanese writing in the process of Islamic knowledge and language through its contributions to the dissemination of religious sciences to the Malaysian Muslim community and the existence of efforts made by various groups in preserving Javanese writing.